The relation between work ethics and work morality and the factors effecting work ethics in work-life - Gök, Sibel (Journal of Human Sciences, 2008)
In recent years, the importance of work ethics and morality has been increased. The effect of them in work-life and their relations with the subjects such as performance, loyalty, competition, etc. have been studied by a number of researchers. The work ethics and morality concepts are becoming widespread in business application, work-life and global trading. Therefore, they appear as a subject for further researches. In this study, the concepts of the work ethics, morality and the development of them in work-life are examined. The differences and similarities between work ethics and morality in terms of quality, content and comprehension etc. are described and discussed. The factors effecting work ethics in work-life, are represented in the light of literature. In our work, we explain and evaluate how the factors such as globalization, culture, social responsibility etc. are effecting it.